2019
DOI: 10.3390/su11061551
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Housing Price Variations Using Spatio-Temporal Data

Abstract: This paper proposes a hedonic regression model to estimate housing prices and the spatial variability of prices over multiple years. Using the model, maps are obtained that represent areas of the city where there have been positive or negative changes in housing prices. The regression-cokriging (RCK) method is used to predict housing prices. The results are compared to the cokriging with external drift (CKED) model, also known as universal cokriging (UCK). To apply the model, heterotopic data of homes for sale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 76 publications
2
29
0
Order By: Relevance
“…The models' prediction errors are relatively equal, which range approximately between 15.1% and 15.9% for validation and cross-validation. The exponential model gives slightly better outcomes in both tests, which coincide with the result found by Tsutsumi et al (2011) as well as Chica-Olmo et al (2019). Figure 7 shows the land price maps for the year 2015 compiled based on officially published observational data.…”
Section: Geostatistical Analysissupporting
confidence: 78%
See 3 more Smart Citations
“…The models' prediction errors are relatively equal, which range approximately between 15.1% and 15.9% for validation and cross-validation. The exponential model gives slightly better outcomes in both tests, which coincide with the result found by Tsutsumi et al (2011) as well as Chica-Olmo et al (2019). Figure 7 shows the land price maps for the year 2015 compiled based on officially published observational data.…”
Section: Geostatistical Analysissupporting
confidence: 78%
“…To assess the estimation accuracy, we performed validation and cross-validation tests based on randomly selected training and testing samples representing 70% and 30% of the samples, respectively. Both tests showed that the exponential model (krig.EXP) gives slightly better results than the Gaussian model (krig.GAU) and the spherical model (krig.SPH), which concur with the conclusions reached by Tsutsumi et al (2011) and Chica-Olmo et al (2019). The second approach for predicting land prices was to employ nine popular ML algorithms split into three categories: (1) linear (GLM, GAMS, and SVMLinear), (2) nonlinear (MARS, kNN, and SVMRadial), and (3) regression tree (Cubist, GBM, and RF).…”
Section: Evaluation Of the Performance Of The Prediction Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…In the literature, many studies have investigated the effects of the aging population [1][2][3][4]. In addition, many studies have investigated housing prices [5][6][7], and these studies have laid the foundation for our research.…”
Section: Introductionmentioning
confidence: 99%